Tsweletso ya tlaiso ya banna dipapading tse di hlaotswego tsa Sesotho sa Lebowa - Mabiletja, Rasekele Selina (University of Limpopo (Turfloop Campus), 2013)
As the topic states, the research is about the abuse of men in the society (Northern Sotho society in particular). Men, like women and children, are also abused, but unlike in the case of women and children, this abuse is not taken seriously. In most of the cases, this abuse is not reported. It is the aim of this study to scrutinize man abuse as depicted in the following Northern Sotho novels: Nonyana ya tokologo (Kekana, 1985), Ke nako ya ka (Molefe, 2001) and Ngwana Magana go botšwa (Motloutsi, 2004).
Thesis (M.A.) --University of Limpopo, 2013
Keywords: Abuse; Family violence; 362.8292; Abused men - South Africa - Limpopo Province; Abused husbands; Psychologically abused men